Type 1–3 Canal Configuration in the Buccal Root of a Maxillary Second Molar - Hui Li; Qiang Wang; Mingwen Fan; Qingan Xu (Case Reports in Dentistry)
Objectives. A major challenge in root canal treatment is the complex and variable root canal system. There are several methods of classification of root canal systems. Herein, we report a case of a maxillary second molar, the root canal system of which could not be classified according to any of the previous methods. Case Report. Cone-beam computed tomography (CBCT), used to visualize the root canal system of a maxillary left second molar with fused roots, revealed a type 1–3 root canal system in the buccal root and a type 1–1 root canal system in the palatal root. A dental operating microscope was used throughout the treatment, and the root canals were successfully obturated. Conclusion. To the best of our knowledge, this is the first report on the classification of buccal roots of maxillary second molars. Clinical Significance. A dental operating microscope and CBCT play a vital role in mapping the root canal system to ensure that no canal is missed.